Governmental Authority in Revoking Conservation Business Licenses: A Case Study of the PT Rimba Raya Dispute - Alfi Pramudita (Indonesian Journal of Administrative Law and Local Government, 2025)
Revocation of business licenses is an administrative legal action taken by the government as a form of supervision of business activities that no longer meet the requirements or violate laws and regulations. The decision to revoke a license that is made without considering the principles of legality and general principles of good governance (AUPB) can lead to legal disputes that end in lawsuits at the State Administrative Court (PTUN). Therefore, the government ensures that the revocation of business licenses is carried out in accordance with applicable legal provisions, by considering principles such as the principles of justice, legal certainty, benefits for the community, etc. The case of PT Rimba Raya Conservation vs KLHK is a relevant example in considering the importance of implementing AUPB. In this case, the revocation of a business license gave rise to a lawsuit at the PTUN because it was considered not to follow transparent procedures and without a clear legal basis. This shows that every state administrative action must be based on clear procedures to avoid legal disputes. This study aims to analyze the government's authority in revoking business licenses, the underlying legal basis, and how the AUPB is applied in decisions to revoke licenses. This study uses a normative legal method with a statutory approach and case studies to identify problems that arise in the revocation of business licenses. The results of the study indicate that the revocation of business licenses must be carried out transparently, based on clear authority and legal basis, and provide space for license holders to submit objections. Thus, the license revocation policy can reflect legal certainty.